IMPROVING THE METHODOLOGY OF TEACHING THE SUBJECT OF PEDAGOGICAL TECHNOLOGY ON THE BASIS OF HYBRID EDUCATION - Jorayeva Nigorakhon Dilshodbek qizi (Modern American Journals, 2025)
This article scientifically analyzes the improvement of the methodology for teaching the course of pedagogical technologies based on hybrid learning. The paper examines the role of hybrid learning models in enhancing the quality of education and how they integrate with pedagogical technologies. The main principles of hybrid learning, its integration with pedagogical technologies, and methods for enhancing educational processes through modern approaches are discussed. The hybrid learning model increases opportunities for independent learning, interactive communication, and the use of technological tools. Additionally, the article explores the scientific foundations and methodological approaches to the effective application of pedagogical technologies. This article may serve as a guide for teachers and specialists working in the field of education to optimize the educational process based on hybrid learning.
Keywords: Pedagogical technologies, hybrid learning, higher education, pedagogical methodology, distance learning, interactive teaching, improving education quality, innovative teaching methods, teaching methodology, personalized learning, education improvement, teacher qualifications, educational process.